The end of the game: emotional responses of older adults to climate crisis and climate mobilizations in Switzerland - Grand, Jérôme (Frontiers in Climate, 2023)
In relation to climate change activism and climate emotions, the youth has captured most of the attention of researchers. This article draws on in-depth face-to-face interviews with people aged 64 and over engaged in pro-environmental behaviors in Switzerland. Through a thematic analysis, we identify eight themes on positive and negative mental states related to the climate crisis and climate-related mobilizations. The qualitative sample shows that older people engage in pro-environmental behaviors, not out of fear of losing access to vital resources, but out of concern for future generations, humanity, and nature. This broad sense of morality is associated with a form of anger for a world that refuses to change. Between generations, emotions vary in intensity but not in nature, and the strategies older adults undertake to mitigate their negative emotions are similar to the strategies mobilized by youth activists. In both cases, anger and fear are powerful negative emotions, and the pleasure, joy, and hope of protesting with like-minded others is a kind of remedy. Older people just face very different constraints and undertake actions that are compatible with their physical and cognitive capacities.